PEMANFAATAN PLATFORM MEDIA SOSIAL UNTUK USAHA MANDIRI PEMUDA BINA BUGIS SQUAD - TRISNIAN IFIANTI; Adi Adi; ENDANG SETIYO ASTUTI (Musyawarah: Jurnal Pengabdian Masyarakat, 2023)
In the contemporary world, technological advancements have paved the way for online businesses to tap into a broader market using the internet and mobile devices. This implementation of Personal Knowledge Management (PKM) aims to achieve two primary objectives: firstly, training the "Bina Bugis Squads" Youth Community, and secondly, empowering them to engage in online selling through social media platforms, including Tokopedia, which facilitates product marketing across the archipelago. Registering on Tokopedia offers distinct advantages such as effective customer reviews and complaint management (UK), ensuring certification and security (SK), competitive product pricing (HP), comprehensive product descriptions (DP), and reliable transportation options (TR). The enthusiasm to provide workshops to several sellers drives them to embrace online selling through social media and diverse platforms like Facebook, Instagram, and the community itself